Dual-Task Effect on Gait in Healthy Adolescents: Association between Health-Related Indicators and DT Performance. Issue 6 (5th October 2021) - Cinar, Eda; Weedon, Benajmin David; Esser, Patrick; Joshi, Shawn; Liu, Yan-Ci; Delextrat, Anne; Meaney, Andy; Collett, Johnny; Springett, Daniella Nicole; Dawes, Helen
Abstract: The purpose of this study was to determine how dual-task (DT) effect on gait differs among adolescents with different fitness and health profiles. The gait performances of 365 adolescents aged 13–14 years were assessed at single and DT walking. The proportional changes in gait parameters from single to dual were regressed against gender, body mass index (BMIz), three components of MABC-2 (balance, aiming &catching and manual dexterity), group (high vs low motor competence), body strength, physical fitness level using multiple regression analyses; and gender and four items of balance subtest of MABC-2 in the secondary analysis. The analyses showed that being female was associated with greater reduction in gait speed and stride length and an increase in double support time and step time; and having lower score in balance was related to greater reduction in gait speed, and cadence, and an increase in step time. Only zig-zag hopping item of the balance subtest was associated with DT effect on gait speed and stride length. No significant relationships were found between DT effect on gait and the rest of the predictors. Females and adolescents with lower level of balance function may be at higher risk of having DT deficit during walking.